Quantitative risk assessment of FMDV introduction in a FMD free country through bone-in beef and offal importation from a FMD free with vaccination country/zone - Brusa, Victoria; Durrieu, María; Van Gelderen, Carlos; Signorini Porchiett, Marcelo Lisandro; Schudel, Alejandro (Elsevier, 2024)
Quantitative risk assessment was used to estimate the risk of introducing foot-and-mouth disease (FMD) through bone-in beef from Argentina (FMD-free with vaccination status) into other FMD-free countries. A stochastic model was built to characterize all the steps from primary production to bone-in beef export and introduction into an FMD-free country. The probability that bone-in beef from at least one animal infected with the FMD virus (FMDV) was exported during a year was 5.27 × 10−3 (95% CI <10−10 – 5.19 x 10–2) or in other words one case in 190 years. The risk of FMDV introduction was sensitive to the probability of an outbreak occurring in Argentina (r [Spearman´s rank correlation] = 0.99) and the number of herds affected during an outbreak (r = 0.10). Additionally, the probability that susceptible animals in the importing country came into contact with infective material (bones) and generated an outbreak was 6.16 × 10−4 (95% CI <10−10 – 6.20 ×10−3) or one FMD outbreak every 1623 years on average. Based on the quantitative risk assessment results, the probability of FMDV introduction into a FMD-free country where vaccination is not practiced from a FMD-free country where vaccination is practiced associated with bone-in beef trade from Argentina was negligible. The risk of an FMD outbreak caused by the potential introduction of the FMDV was associated with the existing conditions in the country. Thus, maintaining the FMD-free status with or without vaccination would not be relevant.